2013
DOI: 10.1002/jsfa.6336
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the volatile profiles of beer using headspace solid‐phase microextraction and gas chromatography–mass spectrometry

Abstract: The SPME-GC-MS analytical method optimized in this study is suitable for characterizing the volatile fingerprint of different beers, especially on the basis of the kind of fermentation (top, bottom or spontaneous), the method of production and the style of the beer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 33 publications
3
49
0
4
Order By: Relevance
“…A study comparing SPME with continuous liquid-liquid extraction/solvent-assisted flavor evaporation (CLLE/SAFE) for lambic beer reported that SPME recovered more esters but CLLE/SAFE recovered a greater number of acid compounds [16]. Others have shown that SPME-GCMS is useful for analysing volatiles in a wide range of beer styles [17].…”
Section: Solid Phase Microextraction Analysis Of Volatilesmentioning
confidence: 99%
See 1 more Smart Citation
“…A study comparing SPME with continuous liquid-liquid extraction/solvent-assisted flavor evaporation (CLLE/SAFE) for lambic beer reported that SPME recovered more esters but CLLE/SAFE recovered a greater number of acid compounds [16]. Others have shown that SPME-GCMS is useful for analysing volatiles in a wide range of beer styles [17].…”
Section: Solid Phase Microextraction Analysis Of Volatilesmentioning
confidence: 99%
“…Spaepen and his colleagues [18] reported finding caproic (hexanoic) acid, caprylic (octanoic) acid, capric (decanoic) acid, isoamyl acetate, ethyl caproate (hexanoate), ethyl caprylate (octanoate), ethyl caprate (decanoate), and phenethyl acetate. Rossi et al [17] used SPME to characterize the volatiles in different types of beer (lambic was not analysed) and reported that volatile fingerprints could be characterized based on the type of fermentation (top versus bottom) and style.…”
Section: Volatile and Semivolatile Compoundsmentioning
confidence: 99%
“…A large Electronic supplementary material The online version of this article (doi:10.1007/s12161-016-0513-7) contains supplementary material, which is available to authorized users. number of volatile compounds have been identified in beer such as alcohols, esters, acids, aldehydes, ketones, hydrocarbons, ethers, sulfur compounds, alicyclic compounds, aromatic compounds, or heterocyclic compounds Charry-Parra et al 2011;Moreira et al 2013;Riu-Aumatell et al 2014;Rossi et al 2014;Saison et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Among them, solid phase microextracion (SPME) has become very popular due to its ease of use, high sensitivity, reproducibility, low cost, and injection into a single uninterrupted process. SPME, especially in combination with headspace (HS), has shown to have applicability to the analysis of volatile compounds in beer (Andrés-Iglesias et al 2015;Gonçalves et al 2014;Rossi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation